Employee Commitment and Culture Organization on Employee Performance - Pramadewi, Arwinence; Roesdi, Rosnelly; Marzolina, Marzolina; Novandalina, Arini; Rivai, Yutiandry (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2024)
This study aims to analyze and examine the influence of employee commitment and cultural organizational factors towards employees of the Job Performance, Regional Secretariat (SetDa) Riau Province both simultaneously (overall test) and partial (individual test). The research method used is verification, while the population in this study is the Regional Secretariat (SetDa) Riau Province based on increasing totaling 402 people. By using the method of proportional stratified random sampling in the sample amount to obtain 40 respondents. While data collection technology is used by the field study and library that includes observation, interviews and question-naires, and to determine the relationship and the influence of an independent variable to the model variables to use Multiple Linear Regression Analysis. The results showed that the calculated results obtained statistically Multiple Correlation Coefficient (R) was 0.8950 with p <0.05 and the coefficient value of Determination (R2) 80.11%. This means that approximately 80.11% of employee commitment and organizational culture factors have a significant influence on employee job performance. Partial test showed that the partial coefficient of determination values contained in the organizational culture variables for (r2) = 54.58% with p = 0.00000 and tresult = 7.515> ttable = 1.678 and ttable variables for employee commitment (r2) = 78, 74% with p = 0.00000 and tresult = 13.196> ttable = 1.678. These results indicate that organizational cultural factors and employee commitment have a significant relationship influence on employee job performance of the Riau Province Regional Secretariat (SetDa).